Association Between Abdominal Aortic Calcification, Bone Mineral Density, and Fracture in Older Women. (9th October 2019) - Lewis, Joshua R; Eggermont, Celeste J; Schousboe, John T; Lim, Wai H; Wong, Germaine; Khoo, Ben; Sim, Marc; Yu, MingXiang; Ueland, Thor; Bollerslev, Jens; Hodgson, Jonathan M; Zhu, Kun; et al.
ABSTRACT: Although a relationship between vascular disease and osteoporosis has been recognized, its clinical importance for fracture risk evaluation remains uncertain. Abdominal aortic calcification (AAC), a recognized measure of vascular disease detected on single‐energy images performed for vertebral fracture assessment, may also identify increased osteoporosis risk. In a prospective 10‐year study of 1024 older predominantly white women (mean age 75.0 ± 2.6 years) from the Perth Longitudinal Study of Aging cohort, we evaluated the association between AAC, skeletal structure, and fractures. AAC and spine fracture were assessed at the time of hip densitometry and heel quantitative ultrasound. AAC was scored 0 to 24 (AAC24) and categorized into low AAC (score 0 and 1, n = 459), moderate AAC (score 2 to 5, n = 373), and severe AAC (score > 6, n = 192). Prevalent vertebral fractures were calculated using the Genant semiquantitative method. AAC24 scores were inversely related to hip BMD ( r s = –0.077, p = 0.013), heel broadband ultrasound attenuation ( r s = –0.074, p = 0.020), and the Stiffness Index ( r s = –0.073, p = 0.022). In cross‐sectional analyses, women with moderate to severe AAC were more likely to have prevalent fracture and lumbar spine imaging‐detected lumbar spine fractures, but not thoracic spine fractures (Mantel‐Haenszel test of trend p < 0.05). For 10‐year incident clinical fractures and fracture‐related hospitalizations, women with moderate to severe AAC (AAC24 score >1) had increased fracture risk (HR 1.48; 95% CI, 1.15 to 1.91; p = 0.002; HR 1.46; 95% CI, 1.07 to 1.99; p = 0.019, respectively) compared with women with low AAC. This relationship remained significant after adjusting for age and hip BMD for clinical fractures (HR 1.40; 95% CI, 1.08 to 1.81; p = 0.010), but was attenuated for fracture‐related hospitalizations (HR 1.33; 95% CI, 0.98 to 1.83; p = 0.073). In conclusion, older women with more marked AAC are at higher risk of fracture, not completely captured by bone structural p redictors. These findings further support the concept that vascular calcification and bone pathology may share similar mechanisms of causation that remain to be fully elucidated © 2019 American Society for Bone and Mineral Research